Questions to consider when caring for patients with ulcerative colitis: Übersicht = Alltagsrelevante Fragen für die Versorgung von Patient*innen mit Colitis ulcerosa - Hasselblatt, Peter; Reindl, Wolfgang; Gauss, Annika; Neeff, Hannes Philipp; Fusco, Stefano; Klaus, Jochen (Zeitschrift für Gastroenterologie, 2023)
Although the management of patients with ulcerative colitis (UC) is well defined by national and international guidelines, there are many debates and open questions related to daily care of UC patients. Here, we aimed to review topics with high clinical relevance including therapy algorithms, potential biomarkers for disease prognosis and response to therapy, the role of interventions targeting the gut microbiota, insights from head-to-head trials, novel UC medications, exit strategies, the impact of COVID19 on UC, care of patients with acute severe disease, cancer screening, and the role of surgery.
Artikel online veröffentlicht: 18. Oktober 2022
Gesehen am 25.06.2024